Coffee shop’s characteristic and factors influence the number of visitors and profit level of popular coffee shops in Banda Aceh city - Suyanti Kasimin (Proceedings of AICS - Social Sciences, 2017)
Development of Coffee shop business as income source and job opportunity for the community in poverty reduction is an important issue and urgent to be implemented recently. Although the demand for coffee shop’s services is increasing in accordance to the culture and lifestyle development, however competition in the coffee business is also increasing. This research aims to analyze factors influence the visitors’ number and the profit level of the coffee shop businesses of popular coffee shops in Banda Aceh City.  By taking 100 respondents from ten popular coffee shops in Banda Aceh City which different locations, accesses, and performances of the coffee shops, hopefully the questions of this research will be answered. The research used Decretive Analysis Method for the visitors’ characteristic and Doubled Regression method for the coffee shop’s performances that influences the number of visitors and the profit level. The result of the research shows that popular coffee shops have good facilities and performances with consumers who are generally young, private company’s employees and students with high education background. Factors that    have positive and significant influence to the visitors’ number and the profit level of the coffee shops are: wide of the coffee shops, interior, and access. And Factors that have negative significant influence are facility and price.  In order to increase the visitor’s number and the business’ profit, the coffee shop’s entrepreneurs should pay attention on the wide of coffee shop, interior, and access to the coffee shops with reasonable facilities and prices.